2013
DOI: 10.1111/cobi.12087
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential to Restore Historic Grazing Ecosystems with Tortoise Ecological Replacements

Abstract: The extinction of large herbivores, often keystone species, can dramatically modify plant communities and impose key biotic thresholds that may prevent an ecosystem returning to its previous state and threaten native biodiversity. A potentially innovative, yet controversial, landscape-based long-term restoration approach is to replace missing plant-herbivore interactions with non-native herbivores. Aldabran giant (Aldabrachelys gigantea) and Madagascan radiated (Astrochelys radiata) tortoises, taxonomically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…These constitute functional megaherbivore reintroductions, as tortoises were the largest native vertebrates on many islands (69). Several studies have documented their successful establishment (70) and found them to improve dispersal and recruitment in endemic trees (71) and suppress invasive plants (72).…”
Section: Current Scientific Basis For Trophic Rewildingmentioning
confidence: 99%
See 1 more Smart Citation
“…These constitute functional megaherbivore reintroductions, as tortoises were the largest native vertebrates on many islands (69). Several studies have documented their successful establishment (70) and found them to improve dispersal and recruitment in endemic trees (71) and suppress invasive plants (72).…”
Section: Current Scientific Basis For Trophic Rewildingmentioning
confidence: 99%
“…25,[70][71][72], and giant tortoise (Chelonoidis spp.) translocations within the Galapagos Islands (e.g., ref.…”
Section: Current Scientific Basis For Trophic Rewildingmentioning
confidence: 99%
“…Recent debates discuss the extent to which species might be substitutable, and hence functions performed by recently extinct species could be reinstated by the translocations of closely related extant species (e.g., Griffiths et al 2013, Hunter et al 2013). An extreme form of this approach is what has been dubbed ''rewilding'' (e.g., Donlan et al 2005), in which functional equivalents of long-extinct but presumably keystone species are introduced to ecosystems.…”
Section: Moving From Compositional To Functional Goals In a Changing mentioning
confidence: 99%
“…Rewilding or assisted migration are potentially promising lines of conservation management strategies that may help restore vanished or threatened ecosystems to islands or continental regions that no longer harbor the tortoises that previously existed there, but were driven into extinction by human exploitation (Truett and Phillips 2009;Griffiths et al 2010Griffiths et al , 2011Griffiths et al , 2013aPedrono et al 2013). These strategies are particularly pertinent in the Mascarene Islands and on Madagascar, as well as in the Galápagos.…”
Section: Island Refugiamentioning
confidence: 99%